Tinjauan Hukum Islam Terhadap Uang Muka Dalam Sewa menyewa Mobil di Himalaya Tour and Travel Surakarta - Hakim, Ziaul; , Drs. Harun, MH.; , Nurul Huda, M. Ag (2016)
The development ofbusiness todays began to turn into practical thing, one of them is car rental service. It is caused by the expensive cost of buying car, so that many people who do not capable to buy it. Car rental have an important role for society today. With a low cost, the societyalready usesthe vehicle without convoluted. Car rental process at Himalaya Tour and Travel after theoccurred of a transaction (contract) between the tenants and the rental owners with expressed verbally andformed of memorandum. In practice the tenant can not take back the down payment when canceling the rental agreement, although there is no agreement with the employers first. The down payment which happens in the car rental Himalaya Tour and Travel is amoney suspension from the total accumulated of car rental. From this phenomenon the author try to trace and examine the views of Islamic law on the implementation of down paymentin the car rental. In writing this essay, the type of research which is used by authoris field research, and studying the problem based on the norms that are taught bynaṣṣand the opinion of Muslim clerics and scholars who are in the books. The techniques of collecting data are observation, interview, and documentation. The data in this study is analized and presented in the form of words, and categorized according to the formulation of the problem, than the last step is the conclusion. Based on the research, the author concludes that in the implementation of the down payment and lease in the car rental in the Himalaya Tour and Travel is valid or allowed according to the terms and the pillars of the Islamic law. Down payments have become a habit as a symbol of commitment in doing business agreement, if undone, it will be difficult for businessmanand most people. Keyword: Islamic Law, Practice Car Rental, Down Payments.